Lao People's Democratic Republic : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Lao People's Democratic Republic. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that the economy of Lao People's Democratic Republic continues to perform well, supported by a favorable external environment and strong flows of foreign direct investment from its dynamic neighbors. Growth in 2017 was supported by the expansion of electricity exports, construction activity and financial services, but moderated to 6.8 percent as a result of the prohibition on illegal logging, tighter credit conditions and fewer tourist arrivals. Looking ahead, the outlook is positive, with growth on the order of 7 percent per year. Downside risks stem from high public debt and deficits, pockets of weakness, and high dollarization in the banking sector, and a vulnerable external position with low gross international reserves.